THE HIDDEN REASON WHY THE REFORMATION SUCCEEDED - Dolan, Patrick (Asian Horizons, 2017)
The reason that the Reformation happened half a millennium ago was not the corruption in the Catholic Church, but a lack of confidence in the authority and ability of the clergy to connect one with God. Contributing to this attitude were the Black Death which disproportionately killed clergy (who had to be replaced quickly by less well-formed clergy) and the Great Western Schism which diminished the respect for the pope. The position arose that one could connect with God without the assistance of a hierarchy or their sacramental powers. Secular rulers took advantage of this new attitude to further their own ambitions.